Stock performance based on sharia stock screening: Comparasion between syariah stock indices of Indonesia and Malaysia - Azhar, Jeihan Ali; Wulandari, Resti (Asian Management and Business Review, 2021)
This study aims to compare the performance of the Islamic stock index in Malaysia and Indonesia using the Sharpe, Treynor and Jensen methods. The findings in this study are the performance of Sharia JII and FBMS stocks in 2014-2019, it can be concluded that the overall Sharpe and Treynor method shows a negative performance value, which means that the performance is not good, whereas when measured using the Jensen Indonesia method it shows a positive performance value. Which means that the performance is good so that Indonesia has a better performance than Malaysia, measured by the Jensen method. Based on the results of different tests, it shows that there are differences in the performance of the two countries in 2014-2019 from each index (Sharpe, Treynor, and Jensen).